2010
DOI: 10.1007/s00586-010-1464-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of severe dystrophic neurofibromatosis scoliosis: an experience of 32 cases

Abstract: The surgical management of severe rigid dystrophic neurofibromatosis curves is a demanding procedure with uncertain results. Several difficulties are present in such patients including a poor bone stock, sharp angulation of these dystrophic curves and dural thinning or ectasia. The aim of this work was to review the clinical and radiographic outcomes of three-dimensional correction of severe rigid neurofibromatosis curves analyzing its efficacy, safety and possible complications. Thirty-two patients were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 28 publications
0
47
1
1
Order By: Relevance
“…20 However, with the use of the thirdgeneration all pedicle screws instrumentation and using posterior release/osteotomies, safe and good correction of the deformity can be achieved. 18,20 In this study, scoliotic curves up to 90 • with flexibility index up to 25% and kyphosis up to 90 • were corrected posteriorly only. Li et al 20 and Deng et al 8 reported similar good results using posterioronly surgery.…”
Section: Used 90mentioning
confidence: 70%
See 2 more Smart Citations
“…20 However, with the use of the thirdgeneration all pedicle screws instrumentation and using posterior release/osteotomies, safe and good correction of the deformity can be achieved. 18,20 In this study, scoliotic curves up to 90 • with flexibility index up to 25% and kyphosis up to 90 • were corrected posteriorly only. Li et al 20 and Deng et al 8 reported similar good results using posterioronly surgery.…”
Section: Used 90mentioning
confidence: 70%
“…8 Anterior-posterior surgery was the traditional treatment of dystrophic NF-1 scoliosis because posterior fixation alone has been associated with increased incidence of failure and loss of correction by many studies. 15,18,19,23,24 But these studies were using either the Harrington distraction rod, hooks system, or hybrid instrumentation. These instrumentation systems rely on fixing only the posterior column and cannot withstand the applied stresses during correction of deformity and during the follow-up period.…”
Section: A B C D E F G H I J Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment strategies remain controversial due to dystrophic vertebral deformity, very thin pedicles, osteoporosis, and rapid progression. 7 Kim et al 6 believed that patients with a dystrophic scoliotic deformity of 20°-40° and kyphotic angle < 50° were simply managed with posterior spinal instrumentation and fusion; to obtain better efficacy of correction and reduce the risk of pseudarthrosis, anteroposterior instrumented fusion was recommended as the most reliable surgical option in the presence of a dystrophic scoliotic deformity greater than 40° or kyphotic angle greater than 50°. 11 However, other authors 1,2 reported that the clinical efficacy of anteroposterior instrumented fusion was still not satisfactory due to severe hyperkyphosis and vertebral rotation in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 Na neurofibromatose tipo 1 as manifestações ortopédicas são frequentes, sendo a escoliose evidente em até cerca de 60% dos doentes afetados. 3 Esta pode manifestar-se de duas formas: deformidades distróficas e deformidades não distróficas.…”
Section: Introductionunclassified